Application of Lacticaseibacillus paracasei and Tetragenococcus halophilus as adjunct starter cultures in Gouda cheese production - Decadt, Hannes; Weckx, Stefan; De Vuyst, Luc (Frontiers in Microbiology, 2026)
Adjunct starter cultures are of interest in pasteurized cheese production as they provide additional flavor, ensure reproducible quality, and enable faster ripening. In the current study, two adjunct culture strains were selected, namely Lacticaseibacillus paracasei LP46, selected out of 49 isolates from mature Gouda cheese, and Tetragenococcus halophilus TH63, selected out of 244 isolates from a Gouda cheese brine. To date, the use of a Tetragenococcus strain in cheese production has not been reported. Both strains were applied in pilot-scale Gouda cheese productions, and the cheeses were investigated up to 32 weeks of ripening by a multiphasic approach encompassing culture-dependent and culture-independent microbiological analysis, meta-metabolomics, and organoleptic evaluations. In the case of the Lacc. paracasei strain, three batches with each time a different primary starter culture mixture were produced to investigate the effect of the primary starter culture mixture on the adjunct starter culture. The adjunct starter culture strains were able to become abundant in the cheeses. Furthermore, both adjunct starter culture strains seemed to repress the Leuconostoc strains from the primary starter culture mixtures. The Lacc. paracasei adjunct starter culture was associated with higher concentrations of acetoin and cadaverine, despite showing no biogenic amine production during the screening process. The T. halophilus adjunct starter culture increased the total amino acid concentration by 55% and also resulted in higher concentrations of acetoin and 2,3-butanedione. However, the organoleptic evaluation could not indicate a significant difference between the negative controls and the cheeses with adjunct starter cultures. Nevertheless, this first application of a Tetragenococcus strain in Gouda cheese showed that T. halophilus seems a promising cheese adjunct starter culture.